2019
DOI: 10.1021/acs.jafc.8b07263
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Stereoisomers of Dill Ether and Wine Lactone by Pleurotus sapidus

Abstract: The white-rot fungus Pleurotus sapidus (PSA) biosynthesizes the bicyclic monoterpenoids 3,6-dimethyl-2,3,3a,4,5,7a-hexahydrobenzofuran (dill ether) (1) and 3,6-dimethyl-3a,4,5,7a-tetrahydro-1-benzofuran-2(3H)-one (wine lactone) (2). Submerged cultures grown in different media were analyzed by gas chromatography−mass spectrometry. The stereochemistry of the formed isomers was elucidated by comparing their retention indices to those of reference compounds by enantioselective multidimensional gas chromatography. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(27 citation statements)
references
References 39 publications
2
24
0
1
Order By: Relevance
“…[155] Other impressive insights relate to the mechanism of formation of 188 in vivo, [156] and to its biosynthesis using the fungus Pleurotus sapidus QuØl. [157] Gaudin discovered that the dihydrogenated analogues 189 possess pleasant coumarin odors,c loser to tonka beans than to coconut. [158] Surprisingly, 189 had been reported already in 1984 as an insect repellent, [159] but found applications in perfumery only in the early 2000s.…”
Section: Spicy and Phenolicmentioning
confidence: 99%
“…[155] Other impressive insights relate to the mechanism of formation of 188 in vivo, [156] and to its biosynthesis using the fungus Pleurotus sapidus QuØl. [157] Gaudin discovered that the dihydrogenated analogues 189 possess pleasant coumarin odors,c loser to tonka beans than to coconut. [158] Surprisingly, 189 had been reported already in 1984 as an insect repellent, [159] but found applications in perfumery only in the early 2000s.…”
Section: Spicy and Phenolicmentioning
confidence: 99%
“…A compound with a comparatively high FD-factor was the bicyclic monoterpenoid dill ether 1 (17, FD 32,768), while dill ether 2 showed a much lower FD factor (20,FD 128). The biosynthesis of these monoterpene ethers as well as of wine lactone (39, FD 2048) by PSA has been reported by Trapp et al, who have shown that these benzofuranoid compounds were formed de novo by the fungus from D-glucose [14]. The biosynthesis of dill ether has also been reported for the fungus Cystostereum murrayi recently [31].…”
Section: Aroma Extract Dilution Analysis and Compound Identificationmentioning
confidence: 73%
“…All of these compounds were also identified in the Citrus medium used for the cultivation of PSA Mk 37. Limonene and linalool have previously been identified in submerged cultures of PSA [14]. Therefore, the monoterpenes' origin might be attributed to both the culture substrate and the fungal metabolism.…”
Section: Aroma Extract Dilution Analysis and Compound Identificationmentioning
confidence: 97%
See 1 more Smart Citation
“…[155] Andere eindrucksvolle Einblicke betreffen den Mechanismus der Biosynthese von 188 [156] sowie dessen Biosynthese durch den Pilz Pleurotus sapidus QuØl. [157] Forschungsergebnisse von Gaudin haben zudem ergeben, dass hydrierte Analoga des Ty ps 189 einen angenehmen cumarinartigen Geruch besitzen, der mehr an Tonkabohnen als an Kokosnuss erinnert. [158] Überraschenderweise wurde 189 schon 1984 als Insektenschutzmittel beschrieben, [159] aber erst Anfang der 2000er Jahre als Riechstoff verwendet.…”
Section: Angewandte Chemieunclassified